2005
DOI: 10.1002/jclp.20208
|View full text |Cite
|
Sign up to set email alerts
|

Expressive writing intervention for young adult cigarette smokers

Abstract: This investigation examined the feasibility and magnitude of the effect of a stress management intervention involving expressive writing as an adjunct to brief office smoking cessation intervention for young adults. Participants aged 18-21 years were randomized to brief office intervention (N=30) or expressive writing plus brief office intervention (N=30). Biochemically confirmed 30-day point-prevalence tobacco abstinence, smoking reduction, perceived stress, negative affect, and treatment compliance were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…The finding that participants in the expressive writing plus brief office condition initially had lower abstinence rates than participants in the brief office condition are reminiscent of those from our prior investigation (i.e., Ames et al, 2005), in which participants completed expressive writing only before cessation. In the earlier study, 6-month abstinence was lower for the expressive writing condition than for the control condition (10% vs. 20%), although this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…The finding that participants in the expressive writing plus brief office condition initially had lower abstinence rates than participants in the brief office condition are reminiscent of those from our prior investigation (i.e., Ames et al, 2005), in which participants completed expressive writing only before cessation. In the earlier study, 6-month abstinence was lower for the expressive writing condition than for the control condition (10% vs. 20%), although this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 45%
“…This is the second published investigation exploring the use of expressive writing for smoking cessation and is an extension of a prior investigation (i.e., Ames et al, 2005). The point-prevalence abstinence rate for participants who received the expressive writing treatment adjunct was significantly higher than for those in the control condition.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The majority of expressive writing studies that focus on writing about stressful events either did not examine health behavior change or did not find behavior change (Ames et al, 2005, 2007; Pennebaker et al, 1988). However, some studies have shown encouraging effects of expressive writing sessions on behavior change.…”
Section: Expressive Writing Interventionsmentioning
confidence: 99%